Analysis and control of the causes of the uplift of the invert of deep tunnels - Chunlin Li; Yan Wu (Discover Applied Sciences)
Abstract When traversing a complex and fractured geological formation, a deep-buried highway tunnel in Yunnan Province encountered a significant uplift problem in the invert. The causes of the tunnel’s uplifted section were analyzed through on-site observations and monitoring of the lining structure’s deformation, combined with numerical simulation methods. The results indicate that the primary factors leading to the invert uplift are the softening of the surrounding rock at the invert base due to water seepage and the high water pressure in the fractured zone. The softening of the surrounding rock is crucial to the safety of the inverted uplift structure. Based on the tunnel’s engineering characteristics and the causes of the invert uplift, remediation measures such as “enhancing the drainage system, grouting with steel flower pipes, and demolishing and replacing the invert” were adopted. These measures effectively controlled the invert uplift. After the remediation, the convergence rate of the secondary lining decreased, and the deformation stabilized, indicating that the invert uplift remediation plan was reasonable and effective